2018
DOI: 10.14336/ad.2017.1214
|View full text |Cite
|
Sign up to set email alerts
|

Hyperphosphatemia Promotes Senescence of Myoblasts by Impairing Autophagy Through Ilk Overexpression, A Possible Mechanism Involved in Sarcopenia

Abstract: In mammalians, advancing age is associated with sarcopenia, the progressive and involuntary loss of muscle mass and strength. Hyperphosphatemia is an aging-related condition involved in several pathologies. The aim of this work was to assess whether hyperphosphatemia plays a role in the age-related loss of mass muscle and strength by inducing cellular senescence in murine myoblasts and to explore the intracellular mechanism involved in this effect. Cultured mouse C2C12 cells were treated with 10 mM beta-glycer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 58 publications
4
35
1
Order By: Relevance
“…Raz et al suggested that chronic age-associated muscle degeneration was associated with higher fibrosis in muscle [31] and the relationship between muscular AGING fibrosis and loss of strength has also been described in several muscular dystrophies [57]. With respect to senescence increased in old mice, previous results from our group [19,45] are in agreement, as they found that old mice had high levels of serum phosphate linked to increased expression of ILK and senescence genes.…”
Section: Agingsupporting
confidence: 87%
See 2 more Smart Citations
“…Raz et al suggested that chronic age-associated muscle degeneration was associated with higher fibrosis in muscle [31] and the relationship between muscular AGING fibrosis and loss of strength has also been described in several muscular dystrophies [57]. With respect to senescence increased in old mice, previous results from our group [19,45] are in agreement, as they found that old mice had high levels of serum phosphate linked to increased expression of ILK and senescence genes.…”
Section: Agingsupporting
confidence: 87%
“…Cellular senescence can be induced prematurely by activated oncogenes, DNA damage and oxidative stress [15,16] as well as by extracellular systemic factors such as hyperosmolarity, high glucose [17] and glycated albumin [18]. In this sense, we have recently described that elevated extracellular phosphate concentration induced senescence in cultured myoblasts, disrupting the autophagy mechanism through ILK overexpression [19].…”
Section: Agingmentioning
confidence: 99%
See 1 more Smart Citation
“…According to another study, impaired transport of amino acids, in particular branched‐chain amino acids, into muscle had a negative effect on protein recycling and energy utilization, which was associated with alterations in phospholipid metabolism . It is also reported that hyperphosphataemia induces senescence of cultured myoblasts by impairing autophagy and activating mTOR through integrin‐linked kinase overexpression, which could be another potential mechanism of sarcopenia …”
Section: Molecular Mechanisms Of Sarcopeniamentioning
confidence: 99%
“…Recently, a human study by Chen et al [15] demonstrated an inverse association between serum phosphate levels and muscle strength. To the best of our knowledge, there is only one in vitro study that investigated the effect of high-phosphate conditions in mouse C 2 C 12 cells [16]. However, they examined how high phosphate levels affected the differentiation of myoblasts to myotubes, indicating that satellite cells differentiate into myotubes during the process of muscle regeneration.…”
Section: Discussionmentioning
confidence: 99%